Prevalence of chronic pain following suburethral mesh sling implantation for post‐prostatectomy incontinence. Issue 4 (1st April 2021) - MacAskill, Findlay; Sheimar, Kieran; Toia, Bogdan; Sri, Denosshan; Seth, Jai; Sharma, Davendra; Hamid, Rizwan; Greenwell, Tamsin; Ockrim, Jeremy; Taylor, Claire; Malde, Sachin; Sahai, Arun
Abstract: Purpose: To evaluate postoperative pain and complications following AdVance™/AdVance™ XP male sling implantation. Materials and Methods: A multi‐center retrospective medical notes review of patients implanted for bothersome post‐prostatectomy incontinence was conducted. All patients were telephoned to provide further information on pain or further complications related to their surgery. Statistical evaluation utilized logistical regression analysis. Additionally, a literature review was conducted reviewing pain outcomes following AdVance™/AdVance™ XP implantation. Results: One‐hundred and twenty‐seven men were reviewed over an 8‐year period. The mean age was 70 years, with mean follow up 52 months. Of those with mild stress urinary incontinence, 45 (79%) had a successful outcome compared to 42 (72%) in the moderate group. Twenty‐nine (23%) men reported postoperative pain, with a mean maximal pain score of 6 (range: 0–10). The majority of pain resolved within 4 weeks (19/29 men). A further seven patients resolved by 3 months. Only three men (2.3%) had chronic pain greater than 3 months, which all resolved by 1 year. Men less than 65 years were more likely to suffer pain ( p = 0.009). Acute urinary retention occurred in 23 (18%) men and correlated significantly with postoperative pain ( p = 0.04). Overactive bladder symptoms, severity of incontinence or radiotherapy were not correlated with postoperative pain. In our cohort, there were no extrusions, divisions, or explantations. Conclusion: Approximately a quarter of men experience pain in the early postoperative period. However, the severity and rates of chronic pain (>3 months) are low (2.3%) but all settle within a year.